IMPROVING SPEAKING SKILLS OF A1 AND A2 LEVEL STUDENTS - Numonjonova Charosxon Nodirbekovna,; Qahhorova Gulnoza Abduqobil qizi,; Umaraliyeva Munojat, (Лучшие интеллектуальные исследования, 2024)
This article highlights that improve A1 and A2 level students' speaking during the lesson, how they can improve speaking level and utilizing of cutting edge-technologies in not only teaching but also their general English.